PENGARUH BOARD INDEPENDENCE, LEVERAGE, DAN FIRM SIZE TERHADAP EARNING MANAGEMENT - Fabian Aprilio; Linda Santioso (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study aims to determine the effect of board independence ( KOMI ), leverage ( DAR ), firm size ( FSIZE ) on earning management. This research method is qualitative with secondary data sources, namely annual reports published by companies listed on the Indonesia Stock Exchange (www.idx.co.id) and company websites during the 2017-2020period. In this study, the sampling technique used purposive sampling. The total number of valid samples is 100 companies. The results showed that there was a negative and significant effect between KOMI on earning management, DAR had no affect on earning management , FSIZE had a positive and significant effect on earning management.